Birth rights and wrongs : how medicine and technology are remaking reproduction and the law - Fox, Dov (New York, NY : Oxford University Press, 2019)
Today, tens of millions of Americans rely on reproductive advances to help them carry out decisions more personal & far-reaching than almost any other they will ever make: They use birth control or abortion to delay or avoid having children; surrogacy or tissue donation to start or grow a family; & genetic diagnosis or embryo selection to have offspring who survive & flourish. This is no less than the medicine of miracles: It fills empty cradles; frees families from disease; & empowers them to plan a life that doesn't include parenthood. But accidents happen: Embryologists miss ailments; egg vendors switch donors; obstetricians tell pregnant women their healthy fetuses will be stillborn. The aftermaths can last a lifetime, yet political & economic forces conspire against regulation to prevent negligence from happening in the first place. This text examines this important topic.
Also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 13, 2019).
Keywords: Human reproduction -- Law and legislation -- United States; Medical personnel -- Malpractice -- United States; Liability (Law) -- United States